1984
DOI: 10.1038/hdy.1984.43
|View full text |Cite
|
Sign up to set email alerts
|

B chromosomes in Rattus fuscipes I. Mitotic and meiotic chromosomes and the effects of B chromosomes on chiasma frequency

Abstract: SUMMARYThe small heterochromatic B chromosomes of Rattus fuscipes assimilis are similar to those described by others in the related species Rattus rattus. They are apparently stable in somatic tissues, but in male meiosis they are liable to non-disjunction. The B chromosomes in R. f assimilis are associated with an increase in the mean cell chiasma frequency, at least in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Moreover, Thomson et al (1984) observed that the B chromosome in R. fuscipes from Australia is morphologically very similar to that of R. rattus from Japan (Yosida, 1977). However, besides origin from a common source, it is also possible that one chromosome from the karyotype particularly prone to polysomy could be a repeated source of new Bs.…”
Section: Origin Of Bs In Mammalsmentioning
confidence: 96%
“…Moreover, Thomson et al (1984) observed that the B chromosome in R. fuscipes from Australia is morphologically very similar to that of R. rattus from Japan (Yosida, 1977). However, besides origin from a common source, it is also possible that one chromosome from the karyotype particularly prone to polysomy could be a repeated source of new Bs.…”
Section: Origin Of Bs In Mammalsmentioning
confidence: 96%
“…In theory B chromosomes could affect dispersal behaviours directly by the action of genes located on the B chromosomes themselves, either autonomously or via effects on genes on the A chromosomes. The C band-positive nature of the B chromosome (Yosida and Sagai, 1973;Thomson et aL, 1984), however, suggests that much of it is constitutively heterochromatic and thus probably carries relatively few active genes, although this requires confirmation.…”
Section: Pr<0001mentioning
confidence: 99%
“…Such random distribution would be achieved if (a) Bs did not pair at first division and moved randomly to either pole (evidence from R. fuscipes male meiosis suggests that is the case; Thomson, 1984).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors consider Bs as «parasitic» (OsTERGREN 1945;NuR 1977) or «selfish» (MATTEWS andJoNES 1982, 1983) with no known function other than that of their own perpetuation and maintenance. The Bs of some species are known to affec~ the frequency and distribution of chiasmata and consequently the phenotypic variation (THOMSON et al 1984;PARKER et al 1990). HIREMATH and MuRTHY (1986) reported the occurrence of a single Bchromosome of two morphological types, each in one population of Guizotia scabra (Vis.)…”
Section: Introductionmentioning
confidence: 99%